Consumer needs and their satiation properties as drivers of the rebound effect: The case of energy-efficient washing machines - Julia Sophie Wörsdorfer (Max Planck Institute of Economics, 2010)
The possibility of the rebound effect to technological progress has triggered a debate in energy economics concerning the usefulness of the promotion of efficiency progress. Until now, a multitude of empirical evidence has been gathered so to assess the magnitude of the effect in the first place. Progress in theoretical research has been rather modest, however. In this paper, we argue for a broadening of the theoretical basis beyond neoclassical consumer theory. We more specifically suggest turning toward consumption theories that deal with consumer needs and learning processes. We postulate that the rebound effect to energy efficiency progress is a special case of behavioral reactions to technological change more in general. Our central hypothesis is that rebound effects will only occur as long as the consumer needs appealed to by the product are not yet satiated. We exemplarily illustrate how to apply these arguments for the case of energyefficient washing machines.
urn:nbn:de:gbv:27-20110628-150519-4
Keywords: 330; rebound effect; consumer needs; washing machines; Konsumentenverhalten; Energiesparen; Waschmaschine; Bedürfnisse